Characterization of residue dissipation of hexaconazole in Chinese cabbage and spring scallion - Ji Won Lee; Jin-Seong Kim; Ji Hyun Park; Hyun Ho Noh; Min Seok Oh; Jin-Hyo Kim; Kyeong-Ae Son (Applied Biological Chemistry)
Abstract The characterization of hexaconazole residues was evaluated through both single and sequential applications in Chinese cabbage and spring scallion. Maximum residue levels following foliar application were determined to be 1.14 mg kg− 1 in the cabbage and 0.04 mg kg− 1 in the scallion, whereas the soil application contributed minimally. Notably, the initial residue in the cabbage was 28 times greater than that observed in the scallion. Fourteen days after the final foliar application, the cabbage exhibited a 3.6-fold increase in fresh weight, compared to a 1.4-fold increase in the scallion. The degradation rates of hexaconazole were calculated at 0.089 day− 1 for the cabbage and 0.207 day− 1 for the scallion, corresponding with degradation half-lives (T1/2) of 7.8 days for the cabbage, which was more than double the 3.4 days for the scallion. Biological T1/2s in vitro were 210 min for the scallion, while the degradation was not detected in the cabbage. Finally, the 50% dissipation times (DT50) were 3.6–3.8 days for the cabbage and 2.0-3.7 days for the scallion after foliar and sequential applications. In addition, hexaconazole exhibited persistence in soil under greenhouse conditions, resulting in the translocation of residues to rotational crops with detected concentrations reaching up to 0.013 mg kg− 1.